Use of geotechnologies to evaluate soil erosion potential in the Pirajibu-mirim basin, São Paulo, Brazil - Frascareli, Daniele [UNESP]; Bochichi, Diego da Cruz [UNESP]; Martins, Antônio Cesar Germano [UNESP]; Rabelo, Davi Rodrigues (Universidade Federal do Rio Grande do Sul, 2023)
Erosion studies in watersheds can help in decision-making and promote measures that support sustainable management, management of activities and mitigation of the phenomenon, avoiding the commitment of multiple potential uses. In this sense, this work aims to estimate soil loss in the Pirajibu-Mirim basin, Sorocaba-SP. Spatial analysis tools (map algebra) were used to calculate soil loss using the Universal Soil Loss Equation (USLE). The results indicated that the years 2003 and 2012 showed the highest values of soil losses above 200 Mg.ha־¹.ano־¹. Soil losses in this basin were associated with the classes with the highest slope and the type of land use and occupation. Therefore, the general analysis of soil loss in the basin led to the conclusion that approximately half of the area has significant soil loss.
Utilização das geotecnologias para avaliação do potencial de erosão do solo na bacia hidrográfica do Rio Pirajibu-mirim, São Paulo, Brasil
Keywords: erosion; Loss of soil; USLE